Pengaruh Keterampilan 4C (Critical Thinking, Creativity, Collaboration, and Communication) Guru Bimbingan dan Konseling terhadap Keterlaksanaan Layanan Dasar Bimbingan dan Konseling di Sekolah - Humairah Azzahrah; Nur Fadhilah Umar; Muhammad Anas (Bulletin of Counseling and Psychotherapy, 2022)
This study aims to determine the direct and indirect effect of 4c skills (communication, collaboration, and critical thinking through the skills of guidance and counselling teachers on implementing basic guidance and counselling services in Makassar City Junior High Schools. This research method uses a quantitative approach with a correlational research design that aims to investigate the extent to which a variable is related to one or more variables. The research data were collected using research instruments, namely the BK teacher's 4C skill questionnaire and the implementation of basic guidance and counseling services which were distributed to 60 respondents of guidance and counseling teachers, this instrument has been tested for validity and reliability with confirmatory factor analysis, then analyzed using descriptive analysis techniques and path analysis using JASP statistical data. So the results of the research: 1) The description of the implementation of basic services has a high category, 2) The description of the 4C skills of BK teachers from critical thinking variables is in the high category, and creativity, collaboration, and communication are in the medium category, 3) Communication skills BK teacher communication and collaboration have a direct influence on the implementation of basic counselling services but indirectly through creativity, while critical thinking skills have no direct and indirect influence on the implementation of basic counselling services through creativity.